Comparison of Potato Viromes Between Introduced and Indigenous Varieties - Lai, Xianjun; Wang, Haiyan; Wu, Caiyun; Zheng, Wen; Leng, Jing; Zhang, Yizheng; Yan, Lang (Frontiers in Microbiology, 2022)
Viral disease in potatoes has been a major problem in potato production worldwide. In addition to the potential risk of introducing new diseases in new areas, viral-disease epidemics/pandemics can be initiated by “spillover” of indigenous viruses from infected alternative hosts into introduced cultivars. To investigate the tendency of potential viral infection/resistance, we analyzed the viromes of introduced and indigenous varieties of potatoes among different tissues using RNA-seq libraries. Bioinformatics analyses revealed that potato viruses PVM, PVY, and PVS were dominant and the most frequently identified viruses infecting potato virus-free plants in the field, and showed an infection bias between introduced and indigenous cultivars. PVY and PVS were the major viruses in introduced varieties, whereas PVM showed an extraordinarily high percentage in the indigenous variety. Other three common viruses, PVH, potato mop-top virus, and potato leafroll virus were identified specifically in the indigenous variety. There was a tendency for tissue-specific infection and sequence variation in viruses: underground parts (tubers, roots) harbored more unusual viruses, and tubers harbored relatively more variation with a high frequency of single nucleotide polymorphisms than other tissues. Taken together, our study provides a comprehensive overview of the composition, distribution, and sequence variation of viruses between introduced and indigenous varieties of potatoes.